The metabolism of amino acids, AsA and abscisic acid induced by strigolactone participates in chilling tolerance in postharvest zucchini fruit - Wang, Lei; Liu, Li; Huang, Anqi; Zhang, Hua; Zheng, Yonghua (Frontiers in Plant Science, 2024)
Zucchini fruit are notably susceptible to chilling injury when stored at low temperatures. The purpose of this experimental investigation was to assess the influence of strigolactone (ST) (5 μmol L -1 ) on mitigating chilling injury and the metabolic changes in amino acids, ascorbic acid, and abscisic acid in zucchini fruit stored at 4 °C. Research findings demonstrated that ST-treated zucchini fruit displayed a significantly higher tolerance to chilling stress compared to the control group. Postharvest ST treatment led to a decrease in weight loss, accompanied by reduced levels of malondialdehyde and relative ion leakage compared to the untreated group. ST immersion significantly boosted the metabolic pathways associated with proline and arginine, affecting both the enzymatic reactions and gene expressions, thus cumulatively increasing the internal concentrations of these amino acids in zucchini fruit. Zucchini treated with ST exhibited an increased concentration of γ-aminobutyric acid (GABA) as a result of augmented activities and elevated transcriptional levels of glutamate decarboxylase (GAD), GABA transaminase (GAT), and succinate semialdehyde dehydrogenase (SSD). In the ST-treated sample, the elevated enzymatic activities and enhanced gene expressions within the ascorbic acid (AsA) biosynthesis pathway worked together to sustain AsA accumulation. The application of ST resulted in a rise in abscisic acid (ABA) concentration, which correspondingly correlated with the induction of both activities and gene expression levels for of crucial enzymes involved in ABA metabolism. Our findings revealed that submerging zucchini fruit in ST could be a highly effective strategy for boosting their chilling tolerance. The alleviation in chilling injury induced by ST may be attributed to the modulation of proline, arginine, GABA, AsA and ABA metabolism.